Modern practices of obtaining higher education in Kazakhstan - Shnarbekova, М. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
This article is devoted to the analysis of social practices in the field of higher education, formed in post-Soviet Central Asian countries, with specific references to Kazakhstan. Kazakhstan was sig-nificantly affected by the collapse of the Soviet system: breaking ties with many leading former Soviet universities entailed irreversible processes in changing of the entire infrastructure of higher education in the country. Last decades to take place the process of reduction of middle level edu-cation and closure of vocational colleges. These has caused a sharp transition of school graduates to higher education unit, thereby increasing its demand. New opportunities allow studying as well as undergoing internships abroad, tuition fee free education based on the state grant. But there is a differentiation in access to quality higher education and increase of economic barriers to obtain it for children from lower-income families. These differences in access contributed to the formation of «elite» and «mass» universities in the educational space of Kazakhstan and the concentration of youth from lower-income families in non-prestigious educational institutions with low tuition fee. Thereby there is a risk that such situation can increase influence of social background on labour market outcomes (salary and occupational status). In the article the significance of the economic capital in the market of higher education and the social consequences of the choice of “affordable” vocational education are analyzed. Key words: higher education, access to education, economic barriers, high-income families, lower income families, family resource potential.